2021
DOI: 10.1186/s40580-021-00253-y
|View full text |Cite
|
Sign up to set email alerts
|

Real-time monitoring of liver fibrosis through embedded sensors in a microphysiological system

Abstract: Hepatic fibrosis is a foreshadowing of future adverse events like liver cirrhosis, liver failure, and cancer. Hepatic stellate cell activation is the main event of liver fibrosis, which results in excessive extracellular matrix deposition and hepatic parenchyma's disintegration. Several biochemical and molecular assays have been introduced for in vitro study of the hepatic fibrosis progression. However, they do not forecast real-time events happening to the in vitro models. Trans-epithelial electrical resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 67 publications
1
29
0
Order By: Relevance
“…It was observed that ECM has a significant impact on the formation of tight junctions. TEER values among different ECMs have a substantial effect on the MPS-based real-time biological assays, as several researchers have employed TEER for estimating cell viability, fibrosis development, and FBS standardization [ 8 , 27 , 28 , 29 ]. It can be concluded that the choice of ECM is vital for developing the most physiologically relevant MPSs.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that ECM has a significant impact on the formation of tight junctions. TEER values among different ECMs have a substantial effect on the MPS-based real-time biological assays, as several researchers have employed TEER for estimating cell viability, fibrosis development, and FBS standardization [ 8 , 27 , 28 , 29 ]. It can be concluded that the choice of ECM is vital for developing the most physiologically relevant MPSs.…”
Section: Resultsmentioning
confidence: 99%
“…After 80 to 90% confluency, the cells were expanded up to 3 passages before seeding and washed with Dulbecco’s phosphate buffer saline (DPBS) (Cat# 14190144, ThermoFisher, Waltham, MA, USA) to remove cell debris and metabolites before adding fresh media. Cells at 90% confluency were trypsinized with 0.05% Trypsin-EDTA solution (Cat# 25300054, Thermo Fisher, USA), then suspended in freshly prepared RPMI-1640 media containing a specified concentration of FBS [ 22 , 33 , 34 , 35 ]. Human primary pulmonary alveolar epithelial cells (HPAEpiC) (Science Cell Research laboratories, Carlsbad, CA, USA) were revived according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Next, it implemented the introduction of a range of sensors inside of the chip, comprehending the device overall. For example, Farooqi et al introduced trans-epithelial electrical resistance (TEER) sensors to follow up on the differentiation of cells within microfluidic devices and the integrity of the epithelial layer [ 100 ]. Different types of sensors were effectively introduced by de Hoyos-Vega et al, where enzymatic assays to analyze media from hepatocytes, beads-based immunoassays to evaluate secretion of specific growth factors, and electrochemical biosensor detecting the biomarkers released by hepatocytes were tested in microfluidic liver-on-chip [ 101 ].…”
Section: Challenges In Designing Liver Disease-on-chip Modelsmentioning
confidence: 99%